2021
DOI: 10.14238/pi61.3.2021.155-64
|View full text |Cite
|
Sign up to set email alerts
|

3-year survival rate in acute lymphoblastic leukemia: comparison of ALL-2006 and ALL-2013 Protocols

Abstract: Background With advances in supportive and risk-stratified therapy, the 5-year survival rate of acute lymphoblastic leukemia has reached 85.5%. The ALL-2006 treatment protocol was modified and renamed the ALL-2013 protocol, with dose and duration changes. Objective To compare outcomes of the ALL-2006 and ALL-2013 protocols, with regards to mortality, remission, relapse, and three-year survival rates. Methods This was retrospective cohort study. Subjects were acute lymphoblastic leukemia (ALL) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Eight studies provided details on the number of deaths in childhood ALL. The mortality rate was highest in a study from Palembang [ 44 ], with 5.3 deaths per 100,000 children. Meanwhile, the lowest mortality rate was given in a study in Jakarta [ 39 ], with 0.44 deaths per 100,000 children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies provided details on the number of deaths in childhood ALL. The mortality rate was highest in a study from Palembang [ 44 ], with 5.3 deaths per 100,000 children. Meanwhile, the lowest mortality rate was given in a study in Jakarta [ 39 ], with 0.44 deaths per 100,000 children.…”
Section: Resultsmentioning
confidence: 99%
“…The mortality of childhood ALL ranges from 0.44 deaths per 100,000 children in one study [ 39 ] to 5.3 deaths per 100,000 children in another study [ 44 ]. The CFR in this study is 3.58%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the previous studies conducted in several cities in Indonesia, which showed that the survival rate of ALL in children ranges from 20% to 60%. [12][13][14] The survival rate in low-middle-income countries based on CONCORD-2 data was 34.3-73.1%. 2,15 Neutropenia was the main cause of death-related treatment enhanced by infection, leading to life-threatening conditions requiring further treatment and may contribute to the delay of therapy during the induction phase.…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival berdasarkan subjek yang mengalami toksisitas kemoterapi hematologi derajat ringan-sedang adalah 64%, sedangkan derajat berat adalah 41%. Angka ini lebih tinggi bila dibandingkan dengan penelitian di Palembang oleh Meirizkia dkk 16 melaporkan secara keseluruhan, tingkat kelangsungan hidup 3 tahun adalah 33%, dengan 41,7% pada kelompok LLA-2006 dan 30,7% pada kelompok LLA-2013. Penelitian tahun 2018 di Makassar selama 4 tahun (48 bulan) pasien LLA pada anak di RSUP Dr. Wahidin Sudirohusodo sebesar 26%.…”
Section: Pembahasanunclassified